A Reexamination of Korea's Trade Flows : What Has Changed and What Explains These Changes? - Cheng, Kevin (IMF Working Papers; Working Paper, 2004)
This paper reexamines Korea's trade flows. Using the standard demand-based models, the paper finds that owing to the increasing share of electrical and electronic products (EEPs) in total exports, the income elasticity of the Korean export demand has fallen sharply while its price elasticity has risen dramatically. This is a curious result, which begs the question of why. Accordingly, an alternative supply-based model shows that the sharp increase in exports of EEPs is mainly due to Korea's remarkable ability to make technological improvements in their production. After reestimating the standard import equation, the paper finds estimates similar to those from previous studies. Since most of these imports are industrial inputs, they are jointly determined by consumption, fixed investment, and exports.